中国加入WTO与产业结构调整 = China's accession to WTO and industrial structure adjustment - 刘志庆 Liu, Zhiqing (2008)
Based on the theory of comparative advantage and the reality of industry structure, this paper analyses the impacts of China’s entry to WTO on her macroeconomics, agriculture, manufacturing, and service industries and suggests adjustment strategies for them.